Choosing the optimal target area for repeated transcranial magnetic stimulation in treating neuropathic pain in spinal cord injury patients: a comparative analysis - Jin, Lihua; Wang, Haonan; Dong, Yifei; Chen, Qian; Li, Linrong; Li, Yongmei (Frontiers in Neurology, 2024)
The specific target area of repeated transcranial magnetic stimulation (rTMS) in treating neuropathic pain resulting from spinal cord injury (SCI-NP) remains uncertain.: Thirty-four participants with SCI-NP were allocated into three groups, namely the motor cortex (M1, A) group, the left dorsolateral prefrontal cortex (LDLPFC, B) group, and the control (sham stimulation, C) group. The intervention was administered totally ten times. Outcome measures assessed pre-(T0) and post-(T1) the intervention, include Numerical Rating scale (NRS), Anxiety (SAS), Depression (SDS), Sleep Quality (PSQI), Brief Pain Inventory (BPI), and impression of change. Results: All outcomes in group A and B significantly changed after intervention (p < 0.05), as well as the delta value (T1-T0) also significantly than group C (p < 0.05). The delta value of SDS in group B was better than A and the change of pain degree in group B was moderate correlated with the change of PSQI (r = 0.575, p < 0.05). Both patients in the group A and B showed significantly impression of change about their received therapy (p < 0.05).Conclusions: Both targets are effective, but LDLPFC is more effective in reducing depression in SCI-NP. Healthcare providers might choosing the suitable area according to the specific attributes of their patients.